Boundaries of the mind: The individual in the fragile sciences: Cognition - Wilson, Robert A (Cambridge University, 2013)
Where does the mind begin and end? Most philosophers and cognitive scientists take the view that the mind is bounded by the skull or skin of the individual. Rob Wilson, in this new book, provides the foundation for the view that the mind extends beyond the boundary of the individual." "The approach adopted offers a unique blend of traditional philosophical analysis, cognitive science, and the history of psychology and the human sciences. There are discussions of the origin of psychology, nativism about the mind, contemporary views of computation, mental representation, consciousness, the metaphysics of mind, the idea of group minds, and how to think about the individual in the cognitive, biological, and social sciences, what Wilson refers to as the fragile sciences. A companion volume Genes and the Agents of Life explores this general theme in the biological sciences." "This book will appeal to a broad swath of professionals and students in philosophy, psychology, cognitive science, and the history of the behavioral and human sciences.